2008
DOI: 10.1007/s00467-008-0756-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomics of acute kidney injury in children after cardiac surgery

Abstract: Acute kidney injury (AKI) is a major complication in children who undergo cardiopulmonary bypass surgery. We performed metabonomic analyses of urine samples obtained from 40 children that underwent cardiac surgery for correction of congenital cardiac defects. Serial urine samples were obtained from each patient prior to surgery and at 4 h and 12 h after surgery. AKI, defined as a 50% or greater rise in baseline level of serum creatinine, was noted in 21 children at 48-72 h after cardiac surgery. The principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 27 publications
0
56
0
1
Order By: Relevance
“…In these applications, statistical pattern recognition techniques were used for data reduction and analysis (23,26,29,41,43), thereby allowing extraction of metabolic information from the complexity of the information-rich data (4,9,14). Although much of this research addressed metabolic variations induced by toxicological exposures (18,24,32), early studies with human plasma demonstrated that 1 H-NMR spectroscopy can also be used to discriminate individuals with cardiovascular disease (4,8,40). In the latter study, differences were apparent in the intensities of proton signals associated with lipids, establishing the utility of NMR spectroscopy for study of physiological variations of lipids (1,15,37).…”
mentioning
confidence: 99%
“…In these applications, statistical pattern recognition techniques were used for data reduction and analysis (23,26,29,41,43), thereby allowing extraction of metabolic information from the complexity of the information-rich data (4,9,14). Although much of this research addressed metabolic variations induced by toxicological exposures (18,24,32), early studies with human plasma demonstrated that 1 H-NMR spectroscopy can also be used to discriminate individuals with cardiovascular disease (4,8,40). In the latter study, differences were apparent in the intensities of proton signals associated with lipids, establishing the utility of NMR spectroscopy for study of physiological variations of lipids (1,15,37).…”
mentioning
confidence: 99%
“…Blinder with colleagues (9) retrospectively studied 430 infants who underwent heart surgery for congenital defects and observed AKI in 52% of patients. Even in the studies published after introduction of RIFLE and AKIN definitions, variability (27%-52%) of AKI incidence has been reported (5, 6,8,9,15). It was difficult to compare SCr and ClCr values of various ages due to wide distribution of specific values.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry-based metabolomics was used in a prospective cohort of pediatric cardiac surgery patients (n = 40). Twenty-one of these children developed acute kidney injury defined as an increase in serum creatinine concentrations 50% or greater from baseline after 48-72 h. Homovanillic acid sulfate (HVA-SO 4 ), a dopamine metabolite was identified as a marker indicating AKI with 90% sensitivity and 95% specificity using a cutoff value of 24 ng/ml at 12 h after surgery [20]. Atzori et al showed a correlation between urinary metabolic profiles and neutrophil gelatinase-associated lipocalin (NGAL) concentration in a cohort of young adults born with extremely lowbirth weight (ELBW), using partial least-squares discriminant analysis [21].…”
Section: Neonatal Kidney Injurymentioning
confidence: 99%